2008
DOI: 10.1097/tp.0b013e31817441d6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Immunogenicity of Human Leukocyte Antigen Class I Alloantigens Using Structural Epitope Analysis Determined by HLAMatchmaker

Abstract: Analysis of recipient HLA type and mismatched-HLA alloantigens using the HLAMatchmaker algorithm allows prediction of immunogenic donor HLA types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 18 publications
4
59
0
1
Order By: Relevance
“…Previous studies by ourselves and others have shown that simply enumerating the number of polymorphic amino acids at continuous and discontinuous sequence positions is useful for predicting the relative immunogenicity of individual HLA mismatches after exposure to alloantigen [3][4][5]36]. The use of sequence information alone, however, provides limited insight into key determinants of B cell epitope immunogenicity, such as the orientation, accessibility, and physiochemical properties of amino acid side chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies by ourselves and others have shown that simply enumerating the number of polymorphic amino acids at continuous and discontinuous sequence positions is useful for predicting the relative immunogenicity of individual HLA mismatches after exposure to alloantigen [3][4][5]36]. The use of sequence information alone, however, provides limited insight into key determinants of B cell epitope immunogenicity, such as the orientation, accessibility, and physiochemical properties of amino acid side chains.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the amino acid sequence of an HLA allele allows insight into its potential peptide binding repertoire and in the context of transplantation, comparison of the sequences of different HLA alleles enables prediction of immunogenicity of a particular HLA mismatch [3][4][5]. Amino acid sequence alone, although it is useful, provides limited insight into the molecular basis of proteinprotein interactions that are mediated in large part by electrostatic properties; [6 -8] electrostatic forces are particularly important determinants of the specificity and affinity of alloantibody binding [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, luminex bead technologies used for the detection of antibodies in antigen, allele or epitope levels for HLA (7)(8)(9) and non-HLA systems (15), and molecular technologies to detect transcript signatures of diverse immunologic changes are broadening our choice of tests (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of unacceptable human leukocyte antigen (HLA) antigen mismatches, risk assessment by assessing the HLA antibodies, combination of desensitization and careful monitoring of posttransplant immunologic events contributed to improve allograft and patient survival (2)(3)(4). For the histocompatibility tests, in addition to conventional complement-dependent lymphocytotoxicity (CDC) crossmatching test (XM) and low resolution HLA typing, technical developments in XM using flow cytometry and HLA antibody detection methods using luminex microbead array have helped to further understand and identify the immunological components involved in alloimmune response (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…При имму-низации антигеном, содержащим «свои» эплеты, выработки антител к ним со стороны реципиента не происходит. И напротив, интенсивность продукции аллоантител коррелирует с количеством «не своих» эплетов, имеющихся в составе несовпадающих до-норских HLA-антигенов [58]. Путем сравнения на-бора «не своих» и «своих» эплетов в HLA-феноти-пе предполагаемого донора относительно фенотипа реципиента можно объективно оценить уровень так называемой «эпитопной нагрузки», по сути, отра-жающей степень тканевой совместимости.…”
Section: антигенность и иммуногенность Hla-молекул парадигма «не своunclassified